Hyperdoc’ing a Legal English Lesson. My First Experience with Hyperdocs (2023)
This article provides an overview of a group of students’ first experience with HyperDocs as a strategy to foster learning English as a Foreign Language (EFL). It then presents students’ insights on their learning experience along with comments and reflections made by their teacher over the process of implementing HyperDocs in a Legal English course at a Colombian private university. This qualitative study involved a focus group, a students’ survey and the students’ artifacts. The findings display the relevance of assisting students in taking control of their own learning process, being critical net surfers and taking advantage of online learning resources.